2019
DOI: 10.1002/adom.201900383
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Protected Dual Bound States in the Continuum in Metamaterials

Abstract: to access extreme confinement of photons into micro-or nanoscale region [3,10,11] above the light line within the radiation continuum. In general, EM wave is usually interpreted in terms of frequency spectrum, and it propagates as a spectral continuum above the light line in different media. Different orders of resonances may be found in the propagating continuum at specific frequencies described by i n n n 0  ω ω γ = + , where the real part indicates resonance frequencies and the imaginary part indicates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
122
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 259 publications
(128 citation statements)
references
References 37 publications
6
122
0
Order By: Relevance
“…The properties of the quasi-BIC Fano resonance, i.e., Q factor and amplitude of the resonance are determined by the structural asymmetry 'd' values. 35,40,44 Figure 1 Here it is noted that the red shift in quasi-BIC Fano state is very small at low analyte thickness. Such a small shift in resonance frequency could be accurately measured only by increased time scan for the terahertz pulse in the THz-TDS measurements.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The properties of the quasi-BIC Fano resonance, i.e., Q factor and amplitude of the resonance are determined by the structural asymmetry 'd' values. 35,40,44 Figure 1 Here it is noted that the red shift in quasi-BIC Fano state is very small at low analyte thickness. Such a small shift in resonance frequency could be accurately measured only by increased time scan for the terahertz pulse in the THz-TDS measurements.…”
mentioning
confidence: 89%
“…In this study, we choose a typical double gap terahertz asymmetric split ring (TASR) as a building block for the metamaterial due to its design flexibility and sharp quasi-BIC Fano resonant spectral feature. 22,35,[40][41][42] A small portion of a large array of two-dimensional planar TASR metamaterial fabricated on a COC substrate is shown in Figure 1 34,35 The TASR arms act as an inductor while the electric field is confined and enhanced locally in the vicinity of the capacitive split gaps. This TASR metamaterial resides on a low refractive index COC substrate, which is a very promising dielectric material with excellent properties such as high chemical resistance, low water absorption, high flexibility, good thin film compatibility (with use of appropriate adhesion layers) and large transparency across terahertz (0.2-2.5 THz) region of the electromagnetic spectrum.…”
mentioning
confidence: 99%
“…In the absence of material losses, BICs have infinite lifetimes and zero linewidths. An approach to trap light in such remarkable electromagnetic modes is to exploit metasurfaces [2][3][4][5][6][7][8][9], i.e., subwavelength arrays (in the nondiffractive region) where only the specular reflection/transmission channels are allowed by symmetry, wherein outgoing specular channels can be suppressed by tuning the parameters of the system in various manners, leading to symmetry-protected BICs. Achieving robust BICs and quasi-BICs will be of great interest for the realization of cavities with arbitrarily high Q-factor and for applications such as lasing and sensing [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that dielectric metasurfaces with broken in-plane symmetry of unit cells can support high Q-factor resonance arising from the distortion of symmetry-protected BIC [25]. Such a BIC-inspired mechanism allows a general strategy to access extremely high Q resonances and giant enhancement of electromagnetic fields [26], realizing many useful functionalities including lasing and biosensing [27,28].…”
Section: Introductionmentioning
confidence: 99%